Integrating communication dimensions into health models: understanding COVID-19 vaccination through multigroup analysis - Collantes-Loo, Jimena (2025)
Introduction: The global COVID-19 pandemic has highlighted the importance of maintaining public engagement with vaccination programs through effective health communication, particularly as initial crisis awareness fades. This study develops and validates an integrated model of vaccination behavior by combining the Theory of Planned Behavior, the Protection Motivation Theory, and the Structural Influence Model of Health Communication with health communication dimensions. Methods: Using partial least squares analysis of survey data from 320 U.S. adults, the research examines how message components influence cognitive appraisals (threat and response efficacy) and how this relationship is moderated by information-seeking behavior, information processing ease, and trust in government. Results: Results confirm the core relationships of the Theory of Planned Behavior in vaccination contexts while revealing a temporal evolution in risk appraisals, with severity and susceptibility showing diminished effects on attitudes. While message components show non-significant direct effects on appraisals in the aggregate sample, these relationships become significant among high information seekers and those with greater trust in government. Additionally, vulnerability-focused messages have differential effects based on chronic health status, positively impacting risk perceptions among vulnerable populations while reducing perceived susceptibility in others. Conclusion: These findings advance the theoretical understanding of health communication and suggest implementing segmented communication strategies based on audience characteristics.